Detection and Quantitative Estimation of Toxic Acrylamide Levels in Selected Potatoes Chips and French Fries from the Libyan Market Using HPLC-UV Method - Khreit, Osama I. G.; Elfowiris, Abdulsalam; Aljali, Abdulrahman A.; Abduljalil, Omukalthum (Al-Mukhtar Journal of Sciences, 2021)
Acrylamide is a potential health hazardous compound occurring in baked and fried food as a result of excessive dry heating during the preparation and/or processing of foods. Exposure to a high level of acrylamide may cause cancer, neurotoxicity, and mutagenicity. In this study, an isocratic reversed-phase high-performance liquid chromatographic (HPLC) method using a C18 column was used for the determination of acrylamide in selected food. The mobile phase consisted of 0.1% formic acid in water: acetonitrile (98:02), and the flow rate was 1.0 mL min-1, elution was monitored at 200 nm. Validation in selected conditions showed that the chosen method is sensitive, selective, precise, and reproducible with a linear detector response for the determination of acrylamide. The limit of detection (LOD), and the limit of quantification (LOQ), were achieved at 0.41μg mL-1 and 1.25 μg mL-1respectively. The proposed method was also applied after validation to the most popular six brands of chips and French fries available in the Libyan market. Acrylamide was extracted by a simplified extraction method avoiding cleanup by solid-phase extraction (SPE), then analyzed by HPLC-UV. The highest level of acrylamide was found in one brand of chips with a concentration of 16.33 μg mL-1, whereas only one of the French fries products analyzed exhibited an acrylamide concentration of 10.26 μg mL-1.